First record of Otter Civet Cynogale bennettii (Mammalia: Carnivora: Viverridae) kept as a pet in Indonesia, representing a possible new threat to the species - Jamie Francis Bernard Bouhuys (Journal of Threatened Taxa, 2019)
-